Metode Antrian guna Meningkatkan Layanan Distribusi pada CV Sarana Prima Lestari Banjarmasin - Adhitya Ari Dwi Cahyo; Huda Sya'rawi (BIMA: Jurnal Bisnis dan Manajemen, 2022)
This study aims to find out about the services that exist at CV Sarana Prima Lestari Banjarmasin. This study uses the POM QM For Windows application in problem solving. At CV Sarana Prima Lestari Banjarmasin the logistics section currently uses the Multiple Channel Query System (M/M/S) queuing model and has a fleet of 8 units for out-of-town deliveries but still cannot distribute goods optimally. Therefore, calculations were carried out using POM QM For windows to determine the optimal number of fleets for distribution. From calculations using the POM QM For Windows application, the optimal number of fleets for the process of distributing goods at CV Sarana Prima Lestari Banjarmasin is 10 fleet units. Procurement planning was carried out because it saw problems in delivery in the form of delays caused by the lack of fleets currently owned by CV Sarana Prima Lestari Banjarmasin.